Hemorrhagic Stroke in Relapsing Polychondritis: A Rare Complication of a Rare Disease - Benjamin Chaucer; Augustus Demanes; Abriella Stone; Venkat Kakollu (Case Reports in Rheumatology)
Background. Relapsing Polychondritis is a rare rheumatologic condition with multisystem involvement. Common presenting symptoms are auricular and nasal chondritis. Common complications include hearing loss and cardiac involvement. An extremely rare complication is neurological involvement. Case report. We present a case of relapsing polychondritis resulting in stroke and discuss the current literature on this condition. Conclusion. To our knowledge, only 6 previous documented cases of stroke secondary to relapsing polychondritis exist in the current literature. This case represents a rare but important complication of relapsing polychondritis.